MIxS-HCR: a MIxS extension defining a minimal information standard for sequence data from environments pertaining to hydrocarbon resources. Issue 1 (December 2016) - Tsesmetzis, Nicolas; Yilmaz, Pelin; Marks, Peter; Kyrpides, Nikos; Head, Ian; Lomans, Bart
Abstract Here we introduce a MIxS extension to facilitate the recording and cataloguing of metadata from samples related to hydrocarbon resources. The proposed MIxS-HCR package incorporates the core features of the MIxS standard for marker gene (MIMARKS) and metagenomic (MIMS) sequences along with a hydrocarbon resources customized environmental package. Adoption of the MIxS-HCR standard will enable the comparison and better contextualization of investigations related to hydrocarbon rich environments. The insights from such standardized way of reporting could be highly beneficial for the successful development and optimization of hydrocarbon recovery processes and management of microbiological issues in petroleum production systems.